Vicegerency in Islamic thought and scripture : towards a Qur'anic theory of human existential function - Lazhar, Chauki (New York, NY : Routledge, 2023)
"This book explores the reasons for the creation of humanity on Earth from the perspective of ancient and contemporary Muslim thinkers, aiming to lay the outlines of a Qur'anic theory of human existential function. The author proceeds from the assumption that, until now, contemporary Islamic scholarship has suffered from the absence of theorisation about a Qur'anic conception of human existential function (vicegerency), lacking a unified philosophical and epistemological frame of reference. Challenging common perceptions among contemporary Muslim reformists regarding the human existential function, the author examines both classical and contemporary thought as well as conducting a thorough and comprehensive analysis of Qur'anic passages that ground the theory of vicegerency within a cosmic scheme. Ultimately, a new approach for understanding the human existential function from within the Qur'anic worldview is proposed. For the first time then, this book offers an integral induction and categorisation of Qur'anic teleological concepts, combining them within a coherent framework that reveals the outlines of a vicegerency theory and a Qur'anic worldview. Suitable for both scholars and laypersons, the book serves as a landmark textbook in the fields of Islamic Philosophy, Theological Anthropology and Qur'anic Studies"--
Keywords: Qurʼan; Theological anthropology; Islam -- Doctrines; Islamic renewal; RELIGION / Islam / Theology; RELIGION / Islam / General; RELIGION / Islam / Koran & Sacred Writings